Archaeological investigations at Kinbane Castle, County Antrim and its Scottish connections - Breen, Colin; Raven, John (Proceedings of the Society of Antiquaries of Scotland, 2015)
Kinbane Castle is positioned at the base of steep cliffs on the north Antrim coast, with views northwards to Rathlin Island and Islay and eastwards to Kintyre. Recent investigations have demonstrated that this headland was fortified in the 1540s by certain MacDonalds who had arrived in Antrim from Islay. The site was built to act as a bridgehead into Ulster as this family, and its associated mercenaries, attempted to establish themselves as a major force amongst the Gaelic lordships of west Ulster. Its occupation was short-lived, since it was effectively abandoned in the 1550s following defacement by English forces and the reconfiguration of MacDonald settlement across north-east Antrim and the Southern Hebrides.